"Dzieci miłości" - powieść antybiedermeierowska = "The Children of Love" - an Anti-biedermeierian Novel - Berkan-Jabłońska, Maria (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article discusses three issues of "The Children of Love", which is the lesser-known novel by Sue.Firstly, it focuses on an attempt to adapt the novel to the needs of popular readers, especially thefemale ones, who were not very sophisticated intellectually and, in literature, they were looking forstrong emotions, pathos, and entertainment. Secondly, it suggests that the novel was a really valuableroman a these because it referred to the significant social problem.
Keywords: Sue, Eugene (pseud.), Sue, Marie-Joseph (1804-1857); literatura francuska - historia - 19 w.; powieść francuska - 19 w.